Representasi Lingkungan Dalam Novel Karya Jemmy Piran: Kajian Ekokritik - Kasmawati Kasmawati; Setya Yuwana Sudikan; Darni Darni; Anas Ahmadi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This research is a qualitative descriptive study examined through literary ecocriticism which aims to: Explain the form of environmental phenomena in the novel Dalam Peluhan Rahim Tanah, Wanita Bermata Gurita by Jemmy Piran; Explain the value of environmental education in reducing environmental damage. The data of this research are words, phrases, clauses, sentences, both narrative and conversational based on the form of environmental phenomena and the value of environmental education. The data source is the novel Dalam Peluhan Rahim Tanah by Jemmy Piran. The data collection techniques used are reading techniques, note-taking techniques, and documentation techniques. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions/verification. The results of the study show that: The representation of the form of environmental phenomena in the novel Dalam Peluhan Rahim Tanah by Jemmy Piran contains pollution, wilderness, disasters, housing/residence, animals and the earth. The representation of environmental education values includes respect for nature, responsibility, compassion and care, cosmic solidarity, not harming nature, simple and harmonious living, justice, democracy, and moral integration.